Bayesian methods for ancestral state reconstruction in morphosyntax: Exploring the history of argument marking strategies in a large language family. Issue 1 (28th May 2022) - Phillips, Joshua; Bowern, Claire
Abstract: Bayesian phylogenetic methods have been gaining traction and currency in historical linguistics, as their potential for uncovering elements of language change is increasingly understood. Here, we demonstrate a proof of concept for using ancestral state reconstruction methods to reconstruct changes in morphology. We use a simple Brownian motion model of character evolution to test how splits in ergative marking evolve across Pama-Nyungan, a large family of Australian languages. We are able to recover linguistically plausible paths of change, as well as rejecting implausible paths. The results of these analyses elucidate constraints on changes that have led to extensive synchronic variation in an interlocking morphological system. They further provide evidence of an ergative–accusative split traceable to Proto-Pama-Nyungan.